Board of Trustee Characteristics, Portfolio Diversification, and Financial Performance of University Pension Funds in Developing Economies (American Journal of Economics and Business Innovation, 2025)
In Kenya, university pension funds have underperformed due to irregular investment returns, non-remittance of contributions, and fund insolvencies. The purpose of this study was to examine the mediating role of portfolio diversification on the relationship between pension fund board characteristics and financial performance in Kenyan universities’ pension funds. The study focused on board size, gender diversity, and financial expertise and their impact on financial performance through the mediator of portfolio diversification. Using an explanatory design, the study analyzed secondary data from 26 universities’ pension funds covering the period 2015–2022 with 208 observations. The theories underpinning the research were Modern Portfolio Theory, Agency Theory and the Resource Dependence Theory. Results showed that board size has a positive influence on financial Performance (β = 0.1306, p < 0.05) but a negative effect on portfolio diversification (β = -0.2879, p < 0.05). Gender diversity enhances financial performance (β = 0.0122, ρ